On approximation of copulas - Tomasz Kulpa (International Journal of Mathematics and Mathematical Sciences)
New sufficient conditions for strong approximation of copulas, generated by sequences of partitions of unity, are given. Results are applied to the checkerboard and Bernstein approximations.